2019
DOI: 10.1530/eje-19-0215
|View full text |Cite
|
Sign up to set email alerts
|

THERAPY OF ENDOCRINE DISEASE: Medical treatment of primary aldosteronism

Abstract: In patients with primary aldosteronism, specific treatment provides prognostic benefit over optimal antihypertensive therapy and is therefore crucial to reduce mortality and morbidity in this subgroup of patients with hypertension. Prognostic relevance has been shown for adrenalectomy in unilateral disease and for medical treatment with mineralocorticoid receptor antagonists in bilateral adrenal hyperplasia. Collectively, evidence points to the superiority of surgical treatment compared to medical treatment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 31 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…The first line MRA is spironolactone acting by direct antagonizing the receptors which effectively lowers PAC. Side effects come along with its affinity to androgen receptor leading to gynecomastia and erectile dysfunction in male and to progesterone receptor leading to menstrual irregularity in female ( 38 ). In the SPARTACUS trial 57% of the patients developed these side effects from spironolactone compared with 1% of the adrenaletomy patients.…”
Section: Discussionmentioning
confidence: 99%
“…The first line MRA is spironolactone acting by direct antagonizing the receptors which effectively lowers PAC. Side effects come along with its affinity to androgen receptor leading to gynecomastia and erectile dysfunction in male and to progesterone receptor leading to menstrual irregularity in female ( 38 ). In the SPARTACUS trial 57% of the patients developed these side effects from spironolactone compared with 1% of the adrenaletomy patients.…”
Section: Discussionmentioning
confidence: 99%
“…Medical therapy was titrated with the aim of controlling hypertension while reducing other antihypertensive medications. The aim was also to achieve normokalemia without the use of potassium supplementation in all patients, although some physicians additionally targeted a high-normal serum potassium of 4.3 mmol/L or greater [ 10 ]. In patients with adequate control of potassium but persistent hypertension, additional antihypertensive medications were added.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, these investigators found that excess risk was only observed in patients with persistent renin suppression, suggesting that renin measurements during medical therapy may reflect adequacy of MR blockade [ 7 , 8 ]. Prior to this, there has been a paucity of evidence on targets for adequate biochemical control, and some experts have suggested targeting a high-normal potassium level [ 9 , 10 ]. Poor tolerance and adherence to medication may explain the poorer outcomes observed with medical therapy.…”
mentioning
confidence: 99%
“…When adrenal venous sampling demonstrates bilateral primary aldosteronism, the general treatment dogma is to prescribe lifelong MR antagonist therapy (2,78). Although the premise for this recommendation is well-intended and based on physiologic principles, it assumes superiority over the potential benefit of non-curative unilateral adrenalectomy to attenuate the severity of disease in certain patients with bilateral primary aldosteronism.…”
Section: Biochemical and Clinical Sequelae Of Noncurative Unilateral mentioning
confidence: 99%
“…When MR antagonist therapy is recommended, we strongly advise counseling on dietary sodium reduction since lowering sodium intake effectively lowers the fuel that modulates disease severity, and is an intervention that when instituted correctly is known to lower blood pressure and increase renin akin to other medical and surgical interventions (Table 1) (78,83). Optimization of MR antagonist therapy requires gradual titration of the dose toward milestones of success (78); normalization of blood pressure, normalization of serum potassium (ideally in the mid-to high-normal range), and ideally normalization (or an unsuppression) of renin (17,78,84). The achievement of these clinical and biochemical benchmarks essentially parallels the outcomes that are expected to be achieved by surgical interventions.…”
Section: A Practical Algorithm For Surgical Indications In Primary Almentioning
confidence: 99%